Optimization Strategy for Battery Swapping Station Scheduling Considering Coupling of Power Market and New Energy Source - WANG Yongli, ZHU Mingyang, ZHANG Yunfei, DONG Huanran, JIANG Sichong, LI Dexin, ZHU Jinrong, GUI Jiangyi (Dianli jianshe)
[Objective] To fully exploit the flexible and adjustable potential of the charging load of a taxi battery swapping station， a charging optimization scheduling strategy is proposed. This strategy aims to ease the conflict between the charging load， peak and valley pressures on the power grid， and new energy consumption. It considers the coupling between the power market and new energy sources. [Methods] The strategy is based on two main goals： providing auxiliary services in the power market and addressing the abandonment and consumption of new energy. A coordinated operation framework is constructed， linking battery swapping stations， power grids， and new energy stations. An optimization mechanism is designed， incorporating peak response， time-of-use tariff matching， and dynamic tracking of battery SOC. Taking 96 time slots as the scheduling granularity， a dual-objective model—maximizing economic benefits and optimizing new energy consumption—was established， and an improved Harris Hawk optimization algorithm was introduced to solve the problem. [Results] Results from a case study show that the proposed strategy increases the economic benefit of the battery swapping station by 25%. It also raises new energy consumption by 16.5%. Additionally， the charging load during grid peak hours is significantly reduced. This helps achieve peak shaving and valley filling. [Conclusions] By dynamically matching new energy abandonment with time-of-use tariffs， the proposed strategy enhances both economic efficiency and the station's ability to consume new energy. It also reduces grid pressure during peak periods. The proposed market-new energy synergy framework offers a new approach for battery swapping stations to participate in power system regulation.